Atomically precise Au144(SR)60 nanoclusters (R = Et, Pr) are capped by 12 distinct ligand types of 5-fold equivalence and display gigantic diastereotopic effects. Issue 47 (14th November 2018) - Dainese, Tiziano; Agrachev, Mikhail; Antonello, Sabrina; Badocco, Denis; Black, David M.; Fortunelli, Alessandro; Gascón, José A.; Stener, Mauro; Venzo, Alfonso; Whetten, Robert L.; Maran, Flavio
Abstract : Short-thiolate-protected Au144 (SR)60 clusters are capped by 12 distinct ligand types of 5-fold equivalence. Abstract : For two decades, Au144 (SR)60 has been one of the most studied and used thiolate (SR) protected gold nanoclusters. In many ways, however, it proved to be a challenging and elusive case, also because of the difficulties in solving its structure by single-crystal X-ray crystallography. We used very short thiols and could prepare Au144 (SC2 H5 )60 and Au144 (SC3 H7 )60 in a very pure form, which was confirmed by UV-vis absorption spectroscopy and very regular electrochemistry patterns. Inductively coupled plasma and electrospray ionization mass spectrometries gave definite proof of the Au144 (SR)60 stoichiometry. High-resolution 1D and 2D NMR spectroscopy in the solution phase provided the result of assessing the presence of 12 ligand types in exactly the same amount (5-fold equivalence). Equally important, we found that the two protons belonging to each methylene group along the thiolate chain are diastereotopic. For the α-CH2 protons, the diastereotopic effect can be indeed gigantic, as it reaches chemical-shift differences of 2.9 ppm. DFT calculations provided insights into the relationship between structure and NMR results. In particular, the 12 ligand types and corresponding diastereotopic effects may be explained by considering the presence of C–H⋯S hydrogen bonds. These results thus provide fundamental insights into the structure of the thiolate layer capping this long-studied gold nanocluster.